The Source of Duncan Campbell Scott’s "Charcoal" - Slonim, Leon (Studies in Canadian Literature, 1979)
Duncan Campbell Scott’s story "Charcoal" was based on events that actually took place. The documentation of the events, as found in newspaper accounts, trial transcripts, and letters from the Indian Agent provide us with a knowledge of the events as Scott himself perceived them and thereby enable us to determine the manner in which he treated the "raw material" of his narrative.